Assessment of Quality of Life among Known Type 2 Diabetics-A Community Based Cross Sectional Study in North Karnataka - Tanuja P Pattankar; Shailaja S Patil (Medsci Publications, 2019)
Introduction: Type 2 DM is a major public health problem in both developing and developed countries. Diabetes and its complications are leading cause for morbidity and mortality, which negatively affects the quality of life. So we conducted this study to assess the QOL of known type 2 diabetics & to understand the association of BMI, Waist circumference, Blood pressure and HbA1c levels with QOL. Materials & Methodology: It's a cross-sectional study done in urban slums, using WHOQOL - BREF scale to assess the QOL, semi - structured questionnaire to assess the socio - demographics; and height, weight, abdominal circumference and blood pressure were measured. HbA1C levels was measured using single use HbA1C Now+ kit. Results: Majority of the study participants were in the age group of 30 - 40 yrs (36.7%). 56% of the study participants were overweight and obese. Hypertension was seen in ≈28%. 12% of them had HbA1c levels >8%. Mean score for QOL in Physical domain was 50.5, Environmental was 50.0, Psychological was 47.0 and Social was 45.8. Factors like depression and HbA1c levels influenced QOL negatively. Perceived QOL was better in males than females, whereas females had better overall QOL domain scores. Conclusion: Low QOL poses one of the major risks in management of Type 2 Diabetes Mellitus. Our study showed half of the study population with poor QOL scores in all domains, which implicate the need for a better care of diabetics with life style modification.